PUBLIC RELATIONS (PR) FOR THE POLITICAL TICKET OF TEDDY RAHMAN-GUSTIANTO (TEGUH) AS CANDIDATES FOR REGENT AND DEPUTY REGENT OF SELUMA, "SELUMA EMAS," AS CHALLENGERS TO THE INCUMBENT CANDIDATES IN THE 2024 SELUMA REGENCY ELECTIONS - Delfan Eko; Hafri Yuliani; Eceh Trisna Ayuh (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2025)
Political Public Relations is an important instrument in building and maintaining a positive image and relationships between political actors and the public and stakeholders. In the context of the 2024 regional elections in Seluma Regency, PR was used to inform, influence, and mobilize public opinion and gain support for certain policies or issues. Strategies for building political image and branding through political PR involved various communication tactics, such as media relations, social media campaigns, press releases, press conferences, and lobbying policymakers. This study highlights the effectiveness of political PR in directing public attention and mobilizing support, as well as the challenges faced in maintaining credibility and trust in the digital information era. This study shows that the success of a winning regional election contest strategy is greatly influenced by the ability of political PR to construct a convincing narrative, build coalitions, and be responsive to evolving issues. Political PR Approaches and Strategies Communication strategies in political public relations (PR) are crucial because they help shape public perception, build reputation, and influence public opinion. Keywords: Must reflect the important concepts in the article.